MULTI-FACETED ANALYSIS OF MTPL PRICE LIBERALIZATIONIN THE RA: STRATEGIES AND MARKET DYNAMICS - Gevorgyan, Yelena; Gulyan, Anahit (Bulletin of Yerevan University G: Economics, 2025)
The Mandatory Third Party Liability (MTPL) insurance in Armenia is pivotal in covering damages caused to third parties by insured vehicles, encompassing both material prejudice and bodily injury compensation. Over its thirteen-year implementation, the system has evolved, with significant changes such as the introduction of bonus-malus (BM) components aimed at fairer risk distribution. However, disparities in the BM system have led to considerable uncollected premiums, exacerbating industry losses. To address this, insurers and regulatory bodies have agreed to liberalize premium calculation models, allowing companies to adopt individualized approaches. With the help of quantitative, comparative and financial statement analysis, this study analyzes the effectiveness of these models, assessing market positions, online sales, and premium trends. Results indicate varying strategies among insurers, with implications for risk assessment and portfolio management.The study underscores the importance of adaptable pricing models in optimizing risk management and profitability in the evolving MTPL landscape. With a firm grasp of the complex interplay between regulatory changes, insurer strategies, and market dynamics, stakeholders can make informed decisions to optimize their competitive positioning and ensure long-term viability in the CMTPL market of Armenia.
Keywords: CMTPL; loss ratio; risk factors; bonus-malus; insurance pricing